Implementación de un sistema de reservaciones e información en línea para la hostería campo duro ecolodge (sireeli) de la provincia insular de Galápagos - Pichucho, Jose (2011)
This research project was born from the need to have a web site with detailed information and also allow make reservations online, as today's globalized world requires as much as possible automate the processes that are carried out and little by little excluding obsolete activities carried into practice in the past. SIREELI is the result of hard work which consists of an analysis and investigation of the needs of the lodge. This site was made based on free software (open source), has two sections: the main one is the same information that is available to internet visitors in the second is the explicit use of the lodge manager and he will q only manipulate the information in the reserves.